Электродинамика: практикум по решению задач - Коротченко К. Б. Константин Борисович; Кунашенко Ю. П. Юрий Петрович; Пивоваров Ю. Л. Юрий Леонидович; Тухфатуллин Т. А. Тимур Ахатович (Томск, Изд-во ТПУ, 2013)
Заглавие с титульного экрана